2011
DOI: 10.3945/ajcn.110.008680
|View full text |Cite
|
Sign up to set email alerts
|

Video game playing increases food intake in adolescents: a randomized crossover study

Abstract: Background: Video game playing has been linked to obesity in many observational studies. However, the influence of this sedentary activity on food intake is unknown. Objective: The objective was to examine the acute effects of sedentary video game play on various components of energy balance. Design: With the use of a randomized crossover design, 22 healthy, normal-weight, male adolescents (mean 6 SD age: 16.7 6 1.1 y) completed two 1-h experimental conditions, namely video game play and rest in a sitting posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
156
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(179 citation statements)
references
References 41 publications
11
156
1
2
Order By: Relevance
“…20 Similarly, in a trial among adolescent boys, ad libitum energy intake after video game play was greater compared with sitting at rest and was not compensated for later in the day. 43 Exposure to food marketing through "advergames" (games developed to advertise a product) or product placement within games may partially explain influences on intake. In a recent trial, children playing advergames containing food cues consumed more energy during a subsequent snack than children playing advergames with nonfood products.…”
Section: Figurementioning
confidence: 99%
“…20 Similarly, in a trial among adolescent boys, ad libitum energy intake after video game play was greater compared with sitting at rest and was not compensated for later in the day. 43 Exposure to food marketing through "advergames" (games developed to advertise a product) or product placement within games may partially explain influences on intake. In a recent trial, children playing advergames containing food cues consumed more energy during a subsequent snack than children playing advergames with nonfood products.…”
Section: Figurementioning
confidence: 99%
“…However, plasma cortisol levels in the 10 children with ASD were not significantly increased in the above described test setting. Video game playing increased sympathetic tone, mental workload, and energy expenditure, however, did not suggest up-regulation of serum cortisol levels [16]. The violent and non-violent TV videogame did not induce significant differences in salivary cortisol levels before and after gaming [17].…”
Section: Discussionmentioning
confidence: 70%
“…Videogame effects are complex and would be better understood as multiple dimensions rather than a simplistic "good-bad" dichotomy [15]. Video game playdid not increase up-regulation of salivary serum [16] or salivary [17] cortisol levels. Moreover, casual videogame decreased physiological stress responses [18].Videogame play may thus not increase plasma or salivary cortisol levels, or decrease physiological stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…A randomised cross-over study found that despite increased levels of energy expenditure while playing video games (mean energy increase compared to rest state = 89kJ) this was counteracted by higher levels of energy intake after playing video games, resulting in an energy surplus of 335kJ compared to those who rested for the same period of time [22].…”
Section: Introductionmentioning
confidence: 99%